Aplikasi Android Kumpulan Lagu-Lagu Perjuangan Nahdlatul Wathan - Yuliadi, Yuliadi; Zaen, Mohammad Taufan Asri; Rodianto, Rodianto; Hifni, Hifni; Zulkhaeri, Zulkhaeri (Forum Kerjasama Pendidikan Tinggi, 2021)
Nahdlatul Wathan is a religious community organization the religious community located on the island of Lombok, West Nusa Tenggara, founded by TGKH. Zaenuddin Abdul Majid. In the period of organizational development, TGKH. Zaenuddin Abdul Majid made a lot of songs with the theme of the NW struggle. Currently, NW's struggle songs have been widely circulated to the general public and the nahdliyin community in various different collections which actually help in taking turns listening. With this, it takes a smartphone device media with an android operating system that is used to listen to all collections of NW struggle songs without space and time limits. With the Android application, these NW struggle songs can make it easier for NW congregations in particular and the public in general to listen to NW struggle songs. In developing the android application, NW's songs of struggle use the waterfall process model whose stages are adopted, namely systems engineering, needs analysis, system design and implementation. System design using UML (Unified Modeling Language) and programming using android studio